PERKEMBANGAN MOTORIK KASAR PADA BALITA DI DUSUN KERET DESA SUMBERJATI KECAMATAN MOJOANYAR KABUPATEN MOJOKERTO - YULISTINA, ASISKA; YUSWO YANI, LASIYATI (JURNAL KEPERAWATAN SEHAT, 2016)
The process of growth and development in infancy and toddlers were a very important process in determined the future of children both physically, mentally and behaviorally. Motor development was one of the most important factors in the development of the individual as a whole. The physical skills children need for activities and sports can be learned and trained in the early days of development. This research aims to determine the gross motor development in children under five years old in Village Keret Sumberjati Mojoanyar District of Mojokerto. The research design used descriptive method. The population in this research were all under five in Dusun Desa Keret Sumberjati Mojoanyar District of Mojokerto regency as many as 43 infants, whereas the samples used in this study as many as 27 respondents drawn by simple random sampling technique. The variables in this research are rough motor development in toddler. Data was collected used DDST sheet and then the data has been collected treated with the stages of editing, coding, scoring, and tabulating. Then presented in the form of frequency distribution table. The results showed that almost half of the respondents had a rough motor development warning of 13 respondents (48.1%) and a small proportion had late gross motor development that was 3 respondents (11.1%). Gross motor development in infants affected by various external and internal factors such as nutritional status, physical activity, and socioeconomic conditions. Educational institutions should make the results of this research provide additional information about the importance of understanding the importance of nutrition in an effort to optimize the gross motor development in infants.Keywords: Motorik Rough, Toddler